2014
DOI: 10.1515/cclm-2012-0850
|View full text |Cite
|
Sign up to set email alerts
|

Plasma advanced glycation end products (AGEs) and NF-κB activity are independent determinants of diastolic and pulse pressure

Abstract: Background: High levels of circulating advanced glycation end products (AGEs) can initiate chronic low-grade activation of the immune system (CLAIS) with each of these factors independently associated with cardiovascular (CV) morbidity and mortality. Therefore, our objective was to characterize the relationship between serum AGEs, CLAIS and other risk factors for CV disease in normotensive non-diabetic individuals. Methods: We measured body mass index (BMI), waistto-hip ratio (WHR), blood pressure, lipid and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
9
1
2
Order By: Relevance
“…This is in contrast with other studies that demonstrated an association between the plasma AGEs, CML, and CEL, and arterial stiffening in other populations. 13,14,[17][18][19] In the case of CML, it has recently been described that the trapping of CML by the RAGE in adipose tissue causes a decrease in AGE plasma levels in individuals with T2DM. 34 Therefore, plasma CML may not be a good reflection of CML accumulation in tissues in individuals with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with other studies that demonstrated an association between the plasma AGEs, CML, and CEL, and arterial stiffening in other populations. 13,14,[17][18][19] In the case of CML, it has recently been described that the trapping of CML by the RAGE in adipose tissue causes a decrease in AGE plasma levels in individuals with T2DM. 34 Therefore, plasma CML may not be a good reflection of CML accumulation in tissues in individuals with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20] Only one case-control study investigated this association in individuals with T2DM. This study found no association between serum pentosidine and heart-brachial pulse-wave velocity or brachialankle pulse-wave velocity after adjustment for renal function.…”
mentioning
confidence: 99%
“…Pulse pressure was calculated by subtracting the diastolic blood pressure from the systolic blood pressure. Mean arterial pressure was computed as diastolic blood pressure + pulse pressure/3 29 . Plasma lipid levels such as total cholesterol, LDL, HDL and triglycerides were measured using a standard commercial enzymatic assay (Beckman Coulter LX20PRO Analyser and Synchron) and Systems Lipid and Multi Calibrators (Beckman Coulter Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
“…AGEs have been reported to be associated with traits including age (Jiang et al, 2012, Lopes-Virella et al, 2012), BMI, and waist to hip ratio (Amin et al, 2011), as well as gender (Jiang et al, 2012, B. K. Kilhovd, 2007) and a range of CVD risk factors including measures of blood pressure (Sourris et al, 2014), smoking (Fukushima et al, 2013), and LDL cholesterol (Lopes-Virella et al, 2012). However, the literature is conflicted.…”
Section: Discussionmentioning
confidence: 99%